Words of foreign origin in political discourse - Zorčič, Sabina (Linguistica (Ljubljana), 2012)
The paper discusses the use of words of foreign origin in Slovenian political discourse. At the outset, this usage is broken down into four groups: the first contains specific phrases and terminology inherent to the political domain; the second contains words of foreign origin generally present in the Slovene language (because of their high frequency of nonexclusivistic use, these words are not of interest to the scope of this investigation); the third contains various words of foreign origin used as affectional packaging for messages with the aim of stimulating the desired interpretation (framing reality); the fourth group, which is the most interesting for our research, is made up of words of foreign origin which could have a marker: + marked, + not necessary, + unwanted, but only if we accept the logic of purism. All the words in this group could be replaced - without any loss of meaning - with their Slovene equivalents. The speaker's motivation for using the foreign word is crucial to our discussion. In the framework of Pierre Bourdieu's poststructural theory as well as Austin's and Searle's speech act theory, statistical data is analysed to observe how usage frequency varies in correlation with selected factors which manifest the speaker's habitus. We argue that words of foreign origin represent symbolic cultural capital, a kind of added value which functions as credit and as such is an important form of the accumulation of capital.
Keywords: discours politique; emprunts; izposojenke; politični diskurz; prevzete besede; Slovene; slovenščina; sociolinguistics; sociolinguistique; sociolingvistika